2018
DOI: 10.24191/mar.v17i1.672
|View full text |Cite
|
Sign up to set email alerts
|

Generic Strategies and Financial Performance Persistence in the Banking Sector in Indonesia

Abstract: This study investigates the relationship between the bank strategic positioning and performance. A central question in the management literature has been to identify the sources of competitive advantage that allow firms to attain and persistent superior performance over their competitors. Bank can build competitive advantages by following either a cost leadership or a differentiation strategy. Bank adopting a cost leadership strategy principally attain advantages based on operational efficiency, and hence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…According to Pehrsson (2016), the key characteristic of the strategy is perceived quality. When the firm succeeds to differentiate itself in attributes that are different from its rivals -for instance in service, quality, style, design, or product features -it becomes the differentiated leader in those particular aspects (Karyani and Rossieta, 2018). The firms in the current study had differentiated themselves in unique quality, service, reputation, and brand.…”
Section: Indicators Of Differentiation Strategymentioning
confidence: 79%
“…According to Pehrsson (2016), the key characteristic of the strategy is perceived quality. When the firm succeeds to differentiate itself in attributes that are different from its rivals -for instance in service, quality, style, design, or product features -it becomes the differentiated leader in those particular aspects (Karyani and Rossieta, 2018). The firms in the current study had differentiated themselves in unique quality, service, reputation, and brand.…”
Section: Indicators Of Differentiation Strategymentioning
confidence: 79%
“…Kim and Lim (1988) found that companies that implemented the generic strategies (cost leadership, differentiation) perform better than the others. Supporting this notion Karyani and Rossieta (2018) found that despite differentiation and cost leadership has a positive effect on financial performance, only cost leadership strategy allows a persistent superior performance in the banking sector. Bayraktar, Hancerliogullari, Cetinguc, and Calisir (2017) also found that differentiation and low-cost leadership strategies have a positive effect on innovation and in turn firm performance.…”
Section: P1 Porters Competitive Strategies (Differentiation and Low-mentioning
confidence: 86%
“…Hal ini dikarenakan strategi diferensiasi tersebut memberikan perusahaan sumber daya yang unggul, menghasilkan perbedaan signifikan dalam kinerja yang optimal. Namun, penelitian ini sejalan dengan penelitian yang dilakukan oleh Karyania & Rossieta (2018) yang membuktikan bahwa strategi biaya rendah memiliki kinerja perusahaan yang lebih baik dibandingkan strategi diferensiasi. Walaupun hasil penelitian menunjukkan bahwa baik strategi biaya rendah maupun diferensiasi berkontribusi positif pada kinerja, namun hanya strategi biaya rendah yang dapat mempertahankan kinerja yang konsisten pada periode berikutnya.…”
Section: Pengaruh Strategi Diferensiasi Terhadap Kinerja Perusahaan L...unclassified